Optical suppression of drug-evoked phasic dopamine release - McCutcheon, James E.; Cone, Jackson J.; Sinon, Christopher G.; Fortin, Samantha M.; Kantak, Pranish A.; Witten, Ilana B.; Deisseroth, Karl; Stuber, Garret D.; Roitman, Mitchell F. (Frontiers in Neural Circuits, 2014)
Brief fluctuations in dopamine concentration (dopamine transients) play a key role in behavior towards rewards, including drugs of abuse. Drug-evoked dopamine transients may result from actions at both dopamine cell bodies and dopamine terminals. Inhibitory opsins can be targeted to dopamine neurons permitting their firing activity to be suppressed. However, as dopamine transients can become uncoupled from firing, it is unknown whether optogenetic hyperpolarization at the level of the soma is able to suppress dopamine transients. Here, we used in vivo fast-scan cyclic voltammetry to record transients evoked by cocaine and raclopride in nucleus accumbens (NAc) of urethane-anesthetized rats. We targeted halorhodopsin (NpHR) specifically to dopamine cells by injecting Cre-inducible virus into ventral tegmental area (VTA) of transgenic rats that expressed Cre recombinase under control of the tyrosine hydroxylase promoter (TH-Cre+ rats). Consistent with previous work, co-administration of cocaine and raclopride led to the generation of dopamine transients in NAc shell. Illumination of VTA with laser strongly suppressed the frequency of transients in NpHR-expressing rats, but not in control rats. Laser did not have any effect on amplitude of transients. Thus, optogenetics can effectively reduce the occurrence of drug-evoked transients and is therefore a suitable approach for studying the functional role of such transients in drug-associated behavior.